2009
DOI: 10.1021/ja809425b
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Bonding-Assisted Self-Doping in Tetrathiafulvalene (TTF) Conductor

Abstract: The synthesis, characterization, and carrier generation mechanism of self-doping in a tetrathiafulvalene (TTF) conductor, ammonium tetrathiafulvalene-2-carboxylate (TTFCOO(-)NH(4)(+)), are described together with molecular orbital characteristics. Insulating TTFCOOH changes into a hole-doped conductor TTFCOO(-)NH(4)(+) with a conductivity of sigma = 2.0 x 10(-4) S/cm (300 K), upon salt formation with NH(3). A radical species, TTF(*+)COO(-)NH(4)(+), is generated via protonation of the TTF moiety as demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 65 publications
2
44
0
Order By: Relevance
“…Most studies of the molecular conductors based on hydrogen bond-functionalized TTF derivatives have focused on the tuning of the molecular self-assembly and the HOMO/LUMO energy levels 47,48 . In this context, several groups have recently reported that the introduction of the hydrogen bond has another important role, that is, the generation of the charge carriers 46,49 . Besides the carrier generation, our system demonstrates that the symmetric hydrogen bond constructs the new type of the purely organic single-component molecular conductors which are composed of highly symmetric molecular units.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of the molecular conductors based on hydrogen bond-functionalized TTF derivatives have focused on the tuning of the molecular self-assembly and the HOMO/LUMO energy levels 47,48 . In this context, several groups have recently reported that the introduction of the hydrogen bond has another important role, that is, the generation of the charge carriers 46,49 . Besides the carrier generation, our system demonstrates that the symmetric hydrogen bond constructs the new type of the purely organic single-component molecular conductors which are composed of highly symmetric molecular units.…”
Section: Discussionmentioning
confidence: 99%
“…The adopted approaches were found to accurately describe the orbital configuration in several earlier studies of different SOMO-HOMO converted radicals [6][7][8] . We find that orbital arrangements obtained using single-reference methods are strongly dependent on the method, basis set, type of wave function and even software code 41 .…”
Section: Methodsmentioning
confidence: 99%
“…1b) 7 and carboxy-TTF crystals (3, Fig. 1c) 8 , the latter representing the first fully organic self-doped molecular conductor. Structure and proposed mechanism of "spin-polarization" 9 of the donor's HOMO in nitronyl nitroxidetetrathiafulvalene compounds 6 .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…43 Electron-rich TTF derivatives can undergo protonationinduced oxidative degradation in the presence of water. 44,45 Moreover, only the first redox reaction (pTTF → pTTF +• ) is accessible in aqueous electrolyte in the potential 'window' within which adsorbed thiols on gold are stable. We therefore sought a water-free electrochemical environment in which to study the single-molecule conductance of 6pTTF6 in the absence of water.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%